Coagulation Signalling and Metabolic Disorders: Lessons Learned from Animal Models - Madhusudhan, Thati; Ruf, Wolfram (Hämostaseologie, 2019)
Nutrient excess in obesity drives metabolic reprogramming in multiple tissues involving extensive interorgan and intercellular crosstalk. Experimental and clinical studies show that prolonged nutrient excess often compromises metabolic adaptation propagating proobesogenic and proinflammatory responses. Chronic inflammation further promotes insulin resistance and associated comorbidities. Obesity and type 2 diabetes are characterized by a hypercoagulable state and clinical studies show a strong correlation of markers of coagulation activation in metabolic disorders. Coagulation protease-dependent signalling via protease-activated receptors is intimately associated with inflammation. The experimental evidence supports roles of tissue factor and G protein coupled protease-activated receptor-2 signalling in the regulation of insulin resistance and metabolic inflammation in diet-induced obesity. Likewise, increases in plasminogen activator inhibitor-1 levels and fibrin-driven inflammation promote insulin resistance in obesity. Additionally, impaired thrombomodulin-dependent protein C activation is mechanistically linked to diabetic kidney disease. Given the increased usage of direct oral anticoagulants, understanding the role of specific coagulation proteases in regulation of metabolic inflammation is highly relevant and might provide insights into the design of novel treatment regimens for patients suffering from thromboinflammatory and cardiometabolic disorders.
Keywords: coagulation proteases; metabolic diseases; protease-activated receptors